Development of a Yoga Program for Type-2 Diabetes Prevention (YOGA-DP) Among High-Risk People in India - Chattopadhyay, Kaushik; Mishra, Pallavi; Manjunath, Nandi Krishnamurthy; Harris, Tess; Hamer, Mark; Greenfield, Sheila Margaret; Wang, Haiquan; Singh, Kavita; Lewis, Sarah Anne; Tandon, Nikhil; Kinra, Sanjay; Prabhakaran, Dorairaj (Frontiers in Public Health, 2020)
Introduction Many Indians are at high-risk of type-2 diabetes mellitus (T2DM). Yoga is an ancient Indian mind-body discipline, that has been associated with improved glucose levels and can help to prevent T2DM. The study aimed to systematically develop a Yoga programme for T2DM prevention (YOGA-DP) among high-risk people in India using a complex intervention development approach. Materials and methods As part of the intervention, we developed a booklet and a high-definition video for participants and a manual for YOGA-DP instructors. A systematic iterative process was followed to develop the intervention and included five steps: (i) a systematic review of the literature to generate a list of Yogic practices that improves blood glucose levels among adults at high-risk of or with T2DM, (ii) validation of identified Yogic practices by Yoga experts, (iii) development of the intervention, (iv) consultation with Yoga, exercise, physical activity, diet, behaviour change and/or diabetes experts about the intervention and (v) pretest the intervention among Yoga practitioners and lay people (those at risk of T2DM and had not practised Yoga before) in India. Results YOGA-DP is a structured lifestyle education and exercise programme, provided over a period of 24 weeks. The exercise part is based on Yoga and includes Shithilikarana Vyayama (loosening exercises), Surya Namaskar (sun salutation exercises), Asana (Yogic poses), Pranayama (breathing practices) and Dhyana (meditation) and relaxation practices. Once participants complete the programme, they are strongly encouraged to maintain a healthy lifestyle in the long-term. Conclusions We systematically developed a novel Yoga programme for T2DM prevention (YOGA-DP) among high-risk people in India. A multi-centre feasibility randomised controlled trial is in progress in India.